Representaciones sociales de las intervenciones para el consumo de drogas en un contexto universitario, Medellín, Colombia (2013)
ABSTRACT: To identify and characterize the social representations of interventions concerning drug use in a university context. Methodology: we used a theoretical model based on symbolic interactionism, interpretive ethnography, and text analysis. Additionally, 27 semi-structured interviews and 7 focus groups were used. The analysis technique used was the reading paradigm proposed by cultural hermeneutics, which is anthropological in nature. Results: intervention appears as the solution to a problem where the prohibitionist paradigm becomes important as a structure of meaning. Education is seen as a social representation and valid alternative to take action against psychoactive drug use. Conclusion: a proposal for taking action against drug use must have the following elements: participation, multidisciplinarity, comprehensiveness, sensitivity, propositional dialogism, the psychosocial dimension, pedagogy, research, education and regulation.